PENGARUH PEMBELAJARAN EXPERIENTIAL LEARNING BERBASIS EKSPLORASI EKOSISTEM BUATAN TERHADAP MOTIVASI BELAJAR SISWA KELAS V UPTD SD 15 BIREUEN - DHARLINA, INTAN; DANIL, M.; ALDYZA, NADIA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This research was motivated by the low learning motivation of students on artificial ecosystem material towards the learning motivation of class V students at UPTD SD Negeri 15 Bireuen.The researcher offers a solution with Experiential Learning with Artificial Ecosystem Exploration. The purpose of this study was to determine the effect of Experiential Learning based on Artificial Ecosystem Exploration on students' learning motivation in science subjects in Class V UPTD SD Negeri 15 Bireuen. The population in this study were all students of Class V UPTD SD Negeri 15 Bireuen consisting of 2 classes totaling 44 students. The sample in this study was all students of class V1 totaling 22 students,Vtotaling 22 students, Class V1 became the experimental class taught using Experiential Learning with Artificial Ecosystem Exploration and class V2 became the control class taught using conventional learning. Data collection techniques in the form of tests and observations. Data analysis techniques using the t-test. The analysis results obtained t count of 2.076 with a t table value of 1.303 at a significance level of 5%, meaning that Experiential Learning has an effect on the understanding of science lessons of grade V students of UPTD SD Negeri 15 Bireuen. The results of observations made by observers on teacher activities obtained an average percentage, which is 93% in the very good category. The results of student activities obtained an average percentage, which is 93%. very good category. The results of the study showed that the significance value Ha was accepted, meaning that PBL based on Artificial Ecosystem Exploration has an effect on students' learning motivation in science lessons of students at V UPTD SD Negeri 15 Bireuen.science lessons of students at V UPTD SD Negeri 15 Bireuen. ABSTRAKPenelian ini dilatarbelakangi pada proses pembelajaran masih kurang maksimal sehingga berdampak pada motivasi belajar siswa yang masih cukup rendah. Peneliti menawarkan solusi dengan pembelajaran Experiential Learning dengan Eksplorasi Ekosistem Buatan. Tujuan penelitian ini untuk mengetahui pengaruh pembelajaran Experiential Learning berbasis Eksplorasi Ekosistem Buatan pada motivasi belajar siswa pelajaran IPA di Kelas V UPTD SD Negeri 15 Bireuen. Populasi dalam penelitian ini adalah seluruh siswa Kelas V UPTD SD Negeri 15 Bireuen yang terdiri dari 2 kelas berjumlah 44 siswa. Sampel dalam penelitian ini adalah seluruh siswa kelas yang berjumlah 22 siswa, yang berjumlah 22 siswa, Kelas V1 menjadi kelas eksperimen yang diajarkan menggunakan pembelajaran Experiential Learning dengan Eksplorasi Ekosistem Buatan dan kelas V2 menjadi kelas kontrol yang diajarkan menggunakan pembelajaran konvensional. Teknik pengumpulan data berbentuk tes dan observasi. Teknik analisis data pengujian uji t. Hasil analsisi diperoleh thitung sebesar 2,076 dengan nilai ttabel sebesar 1,303 pada taraf signifikansi 5%, artinya pembelajaran Experiential Learning berpengaruh terhadap pemahaman pelajaran IPA siswa kelas V UPTD SD Negeri 15 Bireuen. Hasil observasi yang dilakukan pengamat terhadap kegiatan guru diperoleh persentase rata-rata, yaitu 93% kategori sangat baik. Hasil kegiatan siswa diperoleh persentase rata-rata, yaitu 93%. kategori sangat baik. Hasil penelitian menunjukkan bahwa nilai signifikansinya Ha diterima, artinya PBL berbasis Eksplorasi Ekosistem Buatan berpengaruh terhadap motivasi belajar siswa pada pelajaran IPA siswa di V UPTD SD Negeri 15 Bireuen.